“It’s the lecturers to lose”: Examining ‘trust’ in the feedback dialogue - Van Heerden, Martina (Critical Studies in Teaching and Learning, 2025)
“Feedback trust” is an important, though often take-for-granted component of the feedback dialogue. If not maintained, it may be easily lost or broken, which may impact the effectiveness of feedback. In this paper, I unpack the notion of feedback trust by examining what are the factors that enable (or constrain) it, whether feedback trust is automatic, and whether feedback trust can be repaired. The paper is framed by Tschannen-Moran and Hoy’s (2000) conceptualisation of trust. Qualitative data were collected from Honours students in an Arts and Humanities Faculty at a South African university using questionnaires (15) and interviews (6); data were analysed using reflexive thematic analysis. The results broadly indicate that there are three main factors that influence feedback trust: the feedback itself, the feedback giver, and the feedback community. In addition, the results show that feedback trust is to some degree automatic, as it is tied to the role of feedback giver, but that it may strengthen or weaken over time, depending on experience. Lastly, the results show that feedback trust can be repaired through communication, though it depends on how it was broken or lost. This paper outlines that there are four Cs necessary to build, maintain, and repair feedback trust between students and educators: connection, communication, care, and comments.